Diabeł w pismach s. Wandy Boniszewskiej CSA - Damazyn, Michał (Fides, Ratio et Patria. Studia Toruńskie, 2020)
Sister Wanda Boniszewska CSA belongs to the group of Polish mystics of the twentieth century. Her special calling was to sacrifice herself to God, especially for the sins of priests and consecrated persons. Experienced suffering, physical and spiritual, combined with the passion of Christ. From the reading of Boniszewska’s writings it appears that she repeatedly experienced attacks of the evil spirit. The text is an analysis of the content of her Journal.